2017
DOI: 10.1038/s41467-017-01636-8
|View full text |Cite
|
Sign up to set email alerts
|

Ist1 regulates ESCRT-III assembly and function during multivesicular endosome biogenesis in Caenorhabditis elegans embryos

Abstract: Degradation of most integral membrane proteins is directed by the endosomal sorting complex required for transport (ESCRT) machinery, which selectively targets ubiquitin-modified cargoes into intralumenal vesicles (ILVs) within multivesicular endosomes (MVEs). To better understand the mechanisms underlying ESCRT-mediated formation of ILVs, we exploited the rapid, de novo biogenesis of MVEs during the oocyte-to-embryo transition in C. elegans. In contrast to previous models suggesting that ILVs form individuall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
54
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(62 citation statements)
references
References 69 publications
8
54
0
Order By: Relevance
“…Using this approach, we consistently found Hrs in small patches on endosomes ( Fig. 3A), similar to previous findings in other human cell lines and Caenorhabditis elegans using immunogold electron microscopy (24,42,43). Although many larger endosomes harbored several distinct microdomains, suggesting that ILV formation occurs simultaneously at multiple sites, we also found numerous examples of smaller endosomes on which only a single ESCRT-positive endosomal microdomain was visible ( Fig.…”
Section: Components Of the Escrt Machinery Exhibit Distinct Patterns Ofsupporting
confidence: 89%
See 2 more Smart Citations
“…Using this approach, we consistently found Hrs in small patches on endosomes ( Fig. 3A), similar to previous findings in other human cell lines and Caenorhabditis elegans using immunogold electron microscopy (24,42,43). Although many larger endosomes harbored several distinct microdomains, suggesting that ILV formation occurs simultaneously at multiple sites, we also found numerous examples of smaller endosomes on which only a single ESCRT-positive endosomal microdomain was visible ( Fig.…”
Section: Components Of the Escrt Machinery Exhibit Distinct Patterns Ofsupporting
confidence: 89%
“…Based on a large number of genetic and biochemical studies, a consensus has emerged, indicating that the hierarchical assembly of five protein complexes (ESCRT-0, ESCRT-I, ESCRT-II, ESCRT-III, and the Vps4 complex) drives cargo sequestration, membrane bending, and vesicle budding at MVEs (4,(17)(18)(19)(20)(21)(22)(23). In particular, the early-acting ESCRT complexes (ESCRT-0, ESCRT-I, and ESCRT-II) promote clustering of ubiquitin-modified cargoes, while ESCRT-III and Vps4 play critical roles in manipulating membrane curvature to facilitate the inward budding and release of intralumenal vesicles (ILVs) (24)(25)(26)(27)(28)(29)(30). The ESCRT machinery also plays critical roles in several other membrane scission and resealing events, including cytokinetic abscission, plasma membrane repair, retroviral budding, lysosome repair, and nuclear envelope reassembly, each in a topologically similar orientation (31)(32)(33)(34)(35)(36)(37)(38)(39).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…They have been described as acceptors, modulators and enhancers for ESCRT-III-mediated vesicle scission and Vps4 dissociation (Rue et al, 2007;Azmi et al, 2008). Very few studies have revealed phenotypes with single accessory ESCRT-III mutations or knockdowns (Shim et al, 2006;Loncle et al, 2015;Frankel et al, 2017).…”
Section: Rab11-exosome Biogenesismentioning
confidence: 99%
“…Indeed, in the more artificial scenarios that we present here, be it at sites of chm7OPEN accumulation or Chm7 in vps4Δ cells (Figures 6 and 7), there are obvious parallels between the morphologies observed at the INM and those at the plasma membrane (von Schwedler et al, 2003;Hanson et al, 2008;Morita et al, 2011;Cashikar et al, 2014;Jackson et al, 2017), and at endosomes (Adell et al, 2014;Wenzel et al, 2018) in the context of mutants that stall or inhibit membrane scission. They also resemble more physiological circumstances like in the ILVs of A. thaliana (Buono et al, 2017) and C. elegans (Frankel et al, 2017), which resemble beads on a string. The network of INM evaginations also resemble the fenestrated membrane cisternae formed in the ERderived unconventional secretion pathway, CUPS (Curwin et al, 2016).…”
Section: Discussionmentioning
confidence: 98%